Case Report: Chronic Pulmonary Aspergillosis—An Unusual Long-Term Complication of Lung Cancer Treatment - Guziejko, Katarzyna; Klukowska, Katarzyna; Budzińska, Urszula; Mróz, Robert Marek (Frontiers in Medicine, 2022)
Background: Chronic pulmonary aspergillosis (CPA) is a rare complication of radiochemotherapy for lung cancer. It may develop months or years after radical treatment. The diagnosis of CPA is challenging and complex. Not only fungal infection but also cancer relapse always have to be taken under consideration. Antifungal therapy is the base treatment, especially in the case when a surgical procedure is not possible. Standard treatment for at least 6 months is recommended but the optimal duration of the antifungal therapy is unknown. We present the clinical case of CPA, in which we had to perform multidirectional diagnostic tests to confirm the diagnosis and modified treatment due to the recurrence of the disease. Case Presentation: We report a patient who developed CPA three and a half years after concurrent radiochemotherapy for locally advanced non-small-cell lung cancer. Non-specific symptoms were the cause of delayed diagnosis of fungal infection. Samples collected during bronchoscopy allowed to exclude the recurrence of lung cancer and establish the diagnosis of CPA. The patient was treated with itraconazole for 6 months. A few months later, controlled chest CT scans revealed the progression of CPA. Initially, retreatment with itraconazole was implemented. Due to the progression of fungal infection, voriconazole was used in the second line of treatment. Unfortunately, this therapy was complicated by the side effects and deterioration of the patient's condition. The reintroduction of itraconazole resulted in clinical and radiological improvement. Treatment is scheduled for at least 12 months. Conclusion: Chronic pulmonary aspergillosis (CPA) was the cause of clinical deterioration and radiological progression in a patient after the radical treatment of lung cancer. In the described case, the diagnosis of CPA was delayed because of the suspicion of the recurrence of lung cancer. As the surgery was not possible, antifungal therapy with itraconazole was implemented and the proper dosage and duration led to significant clinical improvement.